Interface control of conventional n-type silicon/metal by n-channel organic semiconductor - Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2010)
The rectifying and interface state density properties of n-Si/violanthrone-79/Au metal-diode have been investigated by current-voltage and capacitance-conductance-frequency methods. The ideality factor, barrier height and average series resistance of the diode were found to be 2.07. 0.81 eV and 5.04 k Omega respectively. At higher voltages, the organic layer contributes to I-V characteristics of the diode due to space-charge injection into the organic semiconductor layer and the trapped-charge-limited current mechanism is dominant mechanism for the diode. The barrier height obtained from C-V measurement is lower than the barrier height obtained I-V measurement and the organic layer creates an excess physical barrier for the diode. The interface state density of the diode was found to be 1.70 x 10(11) eV(-1) cm(-2) at 0.2 V and 1.72 x 10(11) eV(-1) cm(-2) at 0.4 V. The obtained electronic parameters indicate that the organic layer provides the conventional n-type silicon/metal interface control option. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Metal-oxide-semiconductor; Organic layer; Interfacial state density